Urban Tourism Destination Image Perception Based on Social Network Analysis: The Example of the Tourist Sites in Yogyakarta - Asep Miftahuddin; R Amalina Dewi Kumalasari; Mahir Pradana (Fakultas Pendidikan Ekonomi dan Bisnis, 2022)
Urban Tourism Destination Image Perception aims to describe the image of urban tourism from the perspective of the perception of tourists, therefore, this study provides new information on the progress and innovation of urban tourism. The model proposed in this study can effectively depict a perceptual picture of a tourist destination, with the conclusion that the research provides a vital referential basis for the development of sustainable urban tourism. Combined with Social network analysis, we built a research framework of image perception of tourism destinations and then took popular online comments of beautiful places in Yogyakarta Travel as an example from twitter data using DroneEmprit. The results show that four aspects are included in tourists' perceptions of the image of the city of Yogyakarta: experience, historical culture, recreational services, and tourist destinations. Among them, the social network of the experiential dimension is the most closely related. In addition, emotional analysis illustrates that tourists' emotional tendencies tend to be positive under the four perceptual dimensions.